Землеробство жителів салтівського селища Коробові Хутори - Горбаненко, С.А.; Колода, В.В.; Пашкевич, Г.О. (Археологія, 2009)
У науковий обіг вводиться нове повноцінне дослідження землеробства носіїв салтівської культури. На прикладі селища Коробові Хутори розглянуто усі складові землеробства, зроблено узагальнювальний аналіз матеріалу. В научный оборот вводится новое исследование земледелия носителей салтовской культуры (середина VIII — середина Х вв.). На примере селища Коробовы Хутора рассмотрены все составляющие земледелия и сделан обобщающий анализ. Полученный материал на фоне хронологических аналогий позволяет говорить о высоком техническом уровне этой отрасли и предположить возможность использования правобережных участков с достаточно ровной для обработки земли поверхностью как с черноземами (на север от селища), так и с грунтами, сформировавшимися под лесной растительностью (на запад, юго-запад и юг). Кроме того, зафиксирована возможность использования левобережной части потенциальной ресурсной зоны. Палеоэтноботанический материал позволяет говорить о существовании озимых и яровых посевов, а также двух- и трехполья. New research on agriculture of Saltivska culture population (from the middle of the 8th to the middle of the 10th centuries) is presented to the scientific circulation. On the example of the Korobovi Khutory settlement all components of farming are examined, and the generalizing analysis is made. The material obtained against a background of chronological analogies allows the authors to conclude about a high technical level of this field and to presume a possibility of usage of right bank areas with surface plain enough for tillage, both with black earth (to the north from the settlement), and with soil formed under the forest vegetation (to the west, south-west, and south). Furthermore, a possibility of usage of the left bank potential source zone is determined. Palaeobotanic material allows the authors to state the existence of winter and spring crops, as well as of two- ad three-field rotation of crops.